Are thigh muscle activation patterns during drop jumps dependent on sex and fatigue? A pilot study in competitive soccer players - Strutzenberger, G.; Zehnder, L.; Borcard, L. M.; Scherr, J.; Spörri, J. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study was to identify whether sex- and fatigue-dependent effects occur in muscle activation patterns during drop jumps. Therefore, 12 (5 female, 7 male) competitive soccer players performed five drop jumps (DJs) in a rested and fatigued state. Lactate, jump height, maximum knee flexion angle and the quadriceps to hamstring muscle activation ratio (QH_GRF ratio) were compared via repeated-measures MANOVA, and effect sizes were used for interpretation. In the fatigued state, jump height and maximum knee flexion angles were reduced (large effect), and the left limb showed an non-significant medium effect towards an increased QH_GRF ratio. Additionally, a sex-specific medium effect of the QH_GRF ratio of the left limb indicates a higher QH_GRF ratio for males. This indicates a tendency towards a quadriceps-dominant landing strategy in at least one limb.